Ionospheric responses to the 21 August 2017 great American solar eclipse – A multi-instrument study - Uma, G.; Brahmanandam, P. S.; Srinivasu, V. K. D.; Prasad, D. S. V. V. D.; Gowtam, V. Sai; Tulasiram, S.; Chu, Y. H. (My University, 2020)
Herein, we report on the ionospheric responses to a total solar eclipse that occurred on 21 August 2017 over the US region. Ground-based GPS total electron content (TEC) data along with ground-based measurements (Millstone Hill Observatory (MHO) and digital ionosondes) and space-based measurements (COSMIC radio occultation (RO) technique) allowed us to identify eclipse-associated ionospheric responses. TEC data at ~20°, ~30°, and ~40°N latitudes from the west to east longitudes show not only considerable depression but also wave-like characteristics in TEC both in the path of totality and away from it, exclusively on the day of eclipse. Interestingly, the observed depressions are associated with lesser (higher) magnitudes at stations over which the solar obscuration percentage was meager (significant), a clear indication of bow-wave-like features. The MHO observes a 30% reduction in F2-layer electron densities between 180 and 220 km on eclipse day. Ionosonde-scaled parameters over Boulder (40.4°N, 100°E) and Austin (30.4°N, 94.4°E) show a significant decrease in critical frequencies while an altitude elevation is seen in the virtual heights of the F-layer only during the eclipse day and that decreases are associated with wave-like signatures, which could be attributed to eclipse-generated waves. The estimated vertical electron density profile from the COSMIC RO-based technique shows a maximum depletion of 40%. Relatively intense and moderate depths of TEC depression, considerable reductions in the F2-layer electron densities measured by the MHO and COSMIC RO-measured densities at the F2-layer peak, and elevations in virtual heights and reduction in the critical frequencies measured by ionosondes during the eclipse day could be due to the eclipse-induced dynamical effects such as gravity waves (GWs) and their associated electro-dynamical effects (modification of ionospheric electric fields due to GWs).
Keywords: Gravity waves; TEC; Ionosondes; Solar eclipse; COSMIC radio occultation technique; Millstone hill observatory